2013
DOI: 10.1098/rsob.130083
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating cell polarity and cell cycle progression: what can we learn from flies and worms?

Abstract: Spatio-temporal coordination of events during cell division is crucial for animal development. In recent years, emerging data have strengthened the notion that tight coupling of cell cycle progression and cell polarity in dividing cells is crucial for asymmetric cell division and ultimately for metazoan development. Although it is acknowledged that such coupling exists, the molecular mechanisms linking the cell cycle and cell polarity machineries are still under investigation. Key cell cycle regulators control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 122 publications
(197 reference statements)
1
36
0
Order By: Relevance
“…Although we cannot rule out the possibility that the array data simply reflect the reduction in the proliferating cell population and the corresponding increase of differentiated cells, it might imply a direct link between cell polarity protein function and proliferative capability through E2F family regulation. Intriguingly, the C. elegans E2F gene is implicated in establishing early embryonic polarity, a process in which apical polarity complex proteins play a major role, consistent with a functional connection (Noatynska et al, 2013;Page et al, 2001;Rabilotta et al, 2015;St Johnston and Ahringer, 2010). Our study therefore firmly establishes that Pals1 serves an essential function in the cell cycle progression of cerebellar progenitor cells, possibly by regulating the E2F family transcriptional network.…”
Section: Cerebellar Progenitors Require Pals1 To Remain In the Cyclinmentioning
confidence: 52%
“…Although we cannot rule out the possibility that the array data simply reflect the reduction in the proliferating cell population and the corresponding increase of differentiated cells, it might imply a direct link between cell polarity protein function and proliferative capability through E2F family regulation. Intriguingly, the C. elegans E2F gene is implicated in establishing early embryonic polarity, a process in which apical polarity complex proteins play a major role, consistent with a functional connection (Noatynska et al, 2013;Page et al, 2001;Rabilotta et al, 2015;St Johnston and Ahringer, 2010). Our study therefore firmly establishes that Pals1 serves an essential function in the cell cycle progression of cerebellar progenitor cells, possibly by regulating the E2F family transcriptional network.…”
Section: Cerebellar Progenitors Require Pals1 To Remain In the Cyclinmentioning
confidence: 52%
“…Since asymmetric distribution of cell-fate determinants enables two daughter cells to follow different fates, the cell cycle may be linked to cell fate through the establishment of cell polarity, as shown in Caenorhabditis elegans and Drosophila melanogaster (Noatynska et al 2013). Previous work has shown that young LT-HSCs undergo both symmetric and asymmetric division and that the precise balance between the two is affected by various signals (Wu et al 2007).…”
Section: A Cell Cycle-dependent Interplay Between Aging and Differentmentioning
confidence: 99%
“…In animals, polarized cells only divide after polarity is fully established, so that polarized elements are correctly segregated into the daughter cells (Noatynska et al, 2013). In stomatal lineage cells, however, how the cell cycle is coordinated with specific cell polarity factors has not been clarified.…”
Section: Discussionmentioning
confidence: 99%